Evaluasi Implementasi Perencanaan Strategi Sistem Informasi Administrasi Kependudukan (SIAK) Menggunakan Process Assessment Model Pada COBIT 5 - Sephia Aldiariza Hernandha; Admaja Dwi Herlambang; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Department of Population and Civil Registration (Dispendukcapil) Malang is a government agency that perform data related to population and civil registration in Malang city. Dispendukcapil has a population administration information system (SIAK) to facilitate the process of data collection and reduce the errors that occur because of human (human error). SIAK is the most important part of Dispendukcapil. There are three problems found in Dispendukcapil Malang, one of them related to the management of resources to SIAK. The process assessment model on COBIT 5 is appropriate to evaluate the management of SIAK resources by focusing on the subdomain of EDM04 ensure resource optimization to determine the current capability level and gap. Based on the results of capability assessment level EDM04 is at level 1 and there is a gap 2. The gap results obtained from the difference between the targeted level of 3 and the existing level is 1. In order for EDM04 ensure resource optimization on SIAK can reach the targeted level ie 3, the recommendation is given establishing principles for protecting existing resources, defining those responsible and authoritative for a process undertaken and defining the resources and information necessary to carry out a process